2011
DOI: 10.1109/tasc.2010.2083620
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Loss, Interstrand Contact Resistance, and Magnetization of Nb$_{3}$Sn Rutherford Cables With Cores of MgO Tape and S-Glass Ribbon

Abstract: Multistrand cables may exhibit two classes of parasitic magnetization both of which can distort the bore-field of an accelerator magnet: (1) a static magnetization ("hysteretic") resulting from intrastrand persistent currents, and (2) a dynamic magnetization produced by interstrand coupling currents generated during field ramping. The latter, which are moderated by the interstrand contact resistances (ICR), can be controlled by the presence of an insulating core inserted between the layers of the cable. Stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…No single physical R c exists if ISCC B 2 and B 6 are to be matched simultaneously, indicating that R c is not uniform across the magnet cross section. Nevertheless, this range is consistent with a R c = 0.33 μΩ measured on a prototype HQ cable without core [30].…”
Section: B Analysis Of the Cross-contact Resistance In Hq01esupporting
confidence: 90%
“…No single physical R c exists if ISCC B 2 and B 6 are to be matched simultaneously, indicating that R c is not uniform across the magnet cross section. Nevertheless, this range is consistent with a R c = 0.33 μΩ measured on a prototype HQ cable without core [30].…”
Section: B Analysis Of the Cross-contact Resistance In Hq01esupporting
confidence: 90%
“…Rc) values we have obtained for uncored Nb3Sn cables have been: 0.24 [9], <0.1 [17], 0.17, 0.37, 0.39 [18], 0.24 [19], 0.37 [20], 0.23 [21], 0.15, 0.36 [22], 0.4 [23], 0.37 [24], 0.22 [25], 0.10, 0.17. 0.25 [26], 0.33 [27] for an average of 0.26 ± 0.1 μΩ along with two "high" values of 1.76 [22] and 1.93 [18]. The sintering together of the Cu surfaces of the Nb3Sn/Cu strands during RHT under pressure is responsible for the very low Rc; clearly a core is needed to separate the Cu/Cu interfaces.…”
Section: A Uncored Nb3sn Cablesmentioning
confidence: 97%
“…The inter-strand resistance is a key parameter that influences the accelerator magnets' dynamic magnetic field quality. Many studies already reported relevant findings in Nb 3 Sn Rutherford cables [93][94][95][96][97][98][99]. However, only a few publications concern the investigation of the inter-strand contact resistance of ReBCO Roebel cables [100][101][102] performed on non-impregnated cables at 77 K. The AC loss performance of such cables is reported as well but mostly investigated at 77 K [50].…”
Section: Introductionmentioning
confidence: 99%